1994
DOI: 10.2514/3.12146
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of surface shear stress vectors using liquid crystal coatings

Abstract: Under normal white light illumination and oblique observation, liquid crystal coating (LCC) color-change response to shear depends on both shear stress magnitude as well as the direction of the applied shear relative to the observer's line of sight. These color-change responses were quantified by subjecting a LCC to a wall-jet shear flow and measuring scattered-light spectra using a fiber optic probe and spectrophotometer. At any fixed shear stress magnitude, the maximum color change was measured when the shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…In this trichromic system, red (R=1, G=0, B=0) was placed at 0°, green (R=0, G=1, B=0) was placed at 120°, and blue (R=0, G=0, B =1) was placed at 240°, respectively. Read et al [8] found that, under normal illumination and fixed above-plane view angle, for a given shear stress magnitude, the maximum hue of shear sensitive liquid crystal coating is measured when the shear vector is aligned with, and directed away from the observer; changes in circumferential angle to either side of the vector aligned position result in symmetric decrease in hue. The hue- change could be well fit by a Gaussian curve between 90° and +90°, or, by a simple second-order polynomial curve over the limited range of 60° and +60°.…”
Section: Transformation Of Color Image To Shear Stress Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trichromic system, red (R=1, G=0, B=0) was placed at 0°, green (R=0, G=1, B=0) was placed at 120°, and blue (R=0, G=0, B =1) was placed at 240°, respectively. Read et al [8] found that, under normal illumination and fixed above-plane view angle, for a given shear stress magnitude, the maximum hue of shear sensitive liquid crystal coating is measured when the shear vector is aligned with, and directed away from the observer; changes in circumferential angle to either side of the vector aligned position result in symmetric decrease in hue. The hue- change could be well fit by a Gaussian curve between 90° and +90°, or, by a simple second-order polynomial curve over the limited range of 60° and +60°.…”
Section: Transformation Of Color Image To Shear Stress Distributionmentioning
confidence: 99%
“…An example of hue- curves for two different shear stress vectors are given in Figure 2. Based on these findings, a surface shear stress measurement methodology was developed [8]. For each physical point on the test surface, a Gaussian curve could be fitted to the hue- data using the follow expression…”
Section: Transformation Of Color Image To Shear Stress Distributionmentioning
confidence: 99%
“…In this trichromic system, red (R=1, G=0, B=0) is placed at 0°, green (R=0, G=1, B=0) is placed at 120°, and blue (R=0, G=0, B =1) is placed at 240°. Read et al [18] found that under normal illumination and fixed above-plane viewing angle, the maximum hue of SSLC coating for a given shear stress magnitude was measured when the shear vector was aligned with, and directed away from, the observer; changes in circumferential angle either side of the vector aligned position resulted in symmetric decrease in hue. The hue-φ change could be well fit by a Gaussian curve between −90° and +90°:…”
Section: Transformation Of Color Image To Shear Stress Distributionmentioning
confidence: 99%
“…Shear-sensitive liquid crystal coating (SSLCC) technique is a non-intrusive global wall shear stress measurement technique. The technique was first studied by Reda et al [ 6 , 7 , 8 , 9 , 10 ] at National Aeronautics and Space Administration (NASA, Washington, DC, USA) Ames Research Center located in Moffett Field, California in the United States. The principle of this technique is to spray a thin layer of shear-sensitive liquid crystal coating onto the tested surface.…”
Section: Introductionmentioning
confidence: 99%